Cardiopatch platform enables maturation and scale-up of human pluripotent stem cell-derived engineered heart tissues - Ilya Y. Shadrin (Nature Portfolio, 2017)
Cardiomyocytes derived from human induced pluripotent stem cells could be used to generate cardiac tissues for regenerative purposes. Here the authors describe a method to obtain large bioengineered heart tissues showing advanced maturation, functional features and engraftment capacity.